Al-Tanasu al-Qur'ani fi Si'ri Ali Ahmad Bakatsir - Mahdi Yousef Mohammad Alshawesh (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2020)
This study aims to study the relationship of Ali Ahmad Bakathir's poetic text with the Quran text in what has been termed intertextuality. The poetic text does not form out of a void and does not go into a void as well. Suffix. The focus is on the poetic performer that this relationship benefited from in the structure of the poem through its reliance on linguistic or artistic interaction, and then the new roles that this text plays in the context of the poetic text, and its ability to crystallize the poets visions. The study investigated the presence of the Quranic text and its mechanisms that are common in Bakathir's poetic text, and emerged from its core functions and semantic dimensions by analyzing and stating its total, partial, or intangible function, or calling the Quranic personality, and clarifying its new roles in the poetic text formats, which concluded with the results are The Quranic text dominated the poetic styles of Bakathir and their diversity, between the total employment of the Quranic text, the partial or the inspiration of Quranic meanings, and the recall of characters and events of the Quranic stories. To enrich his poetic experience, and to contribute to strengthening the literary relationship between his text and the recipient; Because the Noble Quran has a sacred place in hearts, and the poetic text is in harmony with the Quran text, by quoting it or including it up to the quotation based on textualization, or referring to its meanings in order to enhance its stylistic construction, technical and aesthetic functions. Renewal for some purposes, and it calls for characters and events in Quranic stories; To support his poetic experience in dealing with my intention, its significance enriches the poetic text with its semantic and artistic dimensions.